Relationships among self-esteem, depression and self-injury in adolescents: a longitudinal study - Lei, Hui; Xiong, Jingru; Rao, Yuling; Zhu, Ting; Zhang, Xiaocui (Frontiers in Public Health, 2024)
Objective Non-suicidal self-injury is a widespread mental health concern among adolescents. This study aimed to examine the relationship between self-esteem, depression, and self-injury among adolescents using a longitudinal research design. Methods The Self-Esteem Scale (SES), Child Depression Inventory (CDI), and Adolescent Self-Injury Scale (ASIS) were used to follow up 1,265 junior middle school students on three occasions with six-month intervals. Results At all three time points, there were significant gender differences in self-esteem, depression, and self-injury. Self-esteem was negatively correlated with depression and self-injury at all three time points, while depression and self-injury were significantly positively correlated. Cross-lagged analysis revealed that self-esteem at Time 1 (T1) did not significantly predict self-injury at Time 2 (T2), but self-esteem (T2) significantly predicted self-injury at Time 3 (T3; β = −0.079, p < 0.05). Similarly, self-injury (T1) significantly predicted self-esteem (T2; β = −0.140, p < 0.001), and self-injury (T2) significantly predicted self-esteem (T3; β = −0.071, p < 0.01). Horizontal and longitudinal mediating analysis showed that depression served as a complete mediator in both the pathway from self-esteem to self-injury and from self-injury to self-esteem. Cross-lagged analysis showed that self-esteem (T1) significantly predicts depression (T2; β = −0.070, p < 0.05), which in turn predict self-injury (T3; β = 0.126, p < 0.001). Similarly, self-injury (T1) predicted depression (T2; β = 0.055, p < 0.05), which further predicted self-esteem (T3; β = −0.218, p < 0.001). Conclusion The self-esteem, depression, and self-injury of adolescents are closely related; self-esteem and self-injury predict each other; self-esteem indirectly affects self-injury through depression; and self-injury indirectly affects self-esteem through depression. Based on the relationship of bi-directional prediction of self-esteem and self-injury mediated by depression, this study proposes a theoretical model of depression-mediated self-esteem and self-injury cycle.